Introduction: Sexuality, Criminalization, and Social Control - Sears, Clare (Social justice, 2010)
The article introduces this issue, which focuses upon the sexual politics of criminalization both within and beyond the U.S. and contains articles on female sexuality and the U.S. juvenile correctional system, feminist responses to sexual violence in Illinois women’s prisons, and the racial politics of hate crimes in Germany.